The Role of Knowledge Management, Transformational Leadership, and Organizational Commitment on Employee Performance: Empirical Study in Public Sector - Pangaribuan, Leviadi; Satrya, Aryana (Universitas Airlangga, 2024)
Objective: This research aims to empirically investigate the influence of knowledge management practices and transformational leadership on employee performance in the public sector, through the role of organizational commitment as a mediator Design/Methods/Approach: Data were collected using an online questionnaire method from 854 employees. Respondents who meet the requirements in this study are permanent employees with at least one year of work experience from staff level to manager. The collected data were analyzed using Lisrel 8.8 via structural equation modeling (SEM) to explain the relationship between constructs. Findings: The findings of this study showed that both knowledge management and transformational leadership demonstrated a positive and significant effect on employee performance. Organizational commitment positively influenced employee performance, partly mediating the impacts of both knowledge management and transformational leadership on employee performance. Originality/Value: This research sheds light on the role of knowledge management within the Indonesian public sector, a developing country context where previous studies have indicated its rare implementation. Additionally, by combining the role of transformative leadership style as an additional predictor, it can contribute to enriching existing literature. Although previous research has placed organizational commitment as a mediating factor, the integration of this research model has not occurred before, especially in the context of the public sector. Practical/Policy Implication: Public sector organizations are advised to encourage the implementation of knowledge management and create transformative leaders. The synergy between knowledge management and transformational leadership fosters a dynamic workplace environment, enabling employees to be well-prepared, motivated, and empowered to perform effectively in their roles, thereby contributing to organizational success.